Occurrence of enteric parasites and their risk factors among the female inhabitants of lower socioeconomic groups in Dhaka city - Karim, Mt Tahmina; Khanum, Hamida; Musa, Sharmin (Asian Journal of Medical and Biological Research, 2018)
The present study was conducted to investigate the intestinal parasites. A total of 900 female inhabitants of lower socioeconomic groups in Dhaka city were examined during Sep 2013 to Aug 2015, prevalence of gastrointestinal parasitic infestation was 66.22% and 26 parasite species were identified, of which ten species were protozoans, six cestodes, four trematodes and six nematodes. Prevalence of nematoda was the highest (57.55%), then cestode (38.67%), protozoa (19.22%) and lowest was found in trematode (4.11%). Entamoeba histolytica (10.44%) indicates severe faecal contamination among protozoan parasites, while in cestodes Hymenolepis nana (22.78%), in trematodes Fasciolopsis buski (2.11%) and in nematodes Ascaris lumbricoides (38%) were highly prevalent. In twelve study areas, the highest prevalence was found in Kamrangichar (87.5%) and children of age group 1-15 years (75.65%) were mostly affected by intestinal parasite. Asian J. Med. Biol. Res. December 2018, 4(4): 343-350